Flexible Working Time and Work Life Balance of Nursing Officers in Ampara District, Sri Lanka - M. W, MUFASSARA; M.A.G, SAREENA UMMA; M.G.H, SITHY SAFEENA (The journal of contemporary issues in business and government, 2021)
The concept of work life balance (WLB) has considered as a very important phenomena in recent years. Health organizations provide flexible working time (FWT) for nursing officers to enhance their work and family life balance. The primary purpose of this study is to investigate the impact of flexible working time on work life balance. The populationconsists the type “A” base hospitals’ nursing officers in Ampara district, Sri Lanka. Self-rating questionnaire was distributed to 142 nursing offices to gathered data. Among these 128 respondents were returned with duly completed manner. The questionnaire has satisfactory level of validity and reliability. The results showed that strong positive correlation (r = 0.713) exist between the flexible working time and work life balance. Results of simple regression analysis indicated that R square value was 0.508 and adjusted R value was 0.501, these values revealed that around 50% of total variations on work life balance of nursing officers explain by flexible working time. In addition, unstandardized beta value of FWT (b = 0.677) described that, single unit change in FWT leads to 0.677 units change in WLB. The future researcher scan be reproducing this study with large sample size including the related staff in health sector from both public and private hospitals and other effective data gathering techniques like direct interviews and 360 degrees rater measurement scale. According to the importance of FWT on WLB of nursing officers, administrations can consider the recommendations and suggestions given by researcher to enhance the affectivity of existing FWT.